2008
DOI: 10.1016/j.jaapos.2007.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Normative pediatric visual acuity using single surrounded HOTV optotypes on the Electronic Visual Acuity Tester following the Amblyopia Treatment Study protocol

Abstract: Purpose-To provide normative pediatric visual acuity data using HOTV optotypes presented on the Electronic Visual Acuity Tester following the Amblyopia Treatment Study (ATS) protocol.Methods-Monocular testing was conducted on 384 healthy full-term children ranging from 3 to 10 years of age (mean, 5.4 years; SD = 1.8 years). A total of 373 children completed monocular testing of each eye. In addition, 23 adults (mean, 28.7 years; SD = 4.9 years) were tested for comparison. Both monocular visual acuity and inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
73
2
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 88 publications
(83 citation statements)
references
References 24 publications
(2 reference statements)
5
73
2
3
Order By: Relevance
“…Atkinson and Braddick 12 , using Snellen acuity, found that crowded optotype acuity was 58% of that of adults at 5 years of age. Drover et al 24 , using crowded optotypes, found a difference between 7 year olds and 8-10 year olds, but did not comment on whether there was a difference between 8-10 year olds and adults. De Vries and Spekreisje 25 showed data that indicate that the trend line continues upward until the mid-teens, but there was no statistical analysis.…”
mentioning
confidence: 99%
“…Atkinson and Braddick 12 , using Snellen acuity, found that crowded optotype acuity was 58% of that of adults at 5 years of age. Drover et al 24 , using crowded optotypes, found a difference between 7 year olds and 8-10 year olds, but did not comment on whether there was a difference between 8-10 year olds and adults. De Vries and Spekreisje 25 showed data that indicate that the trend line continues upward until the mid-teens, but there was no statistical analysis.…”
mentioning
confidence: 99%
“…However, based on current normative visual acuity data, 13 and as recommended in the current AAPOS screening guidelines, 9 the JVAS has been updated to feature a 20/50-sized optotype as the pass threshold for 3-year-olds. Similarly, current normative visual acuity data 13,14 indicate a pass threshold of 20/32 for 5-year-olds, whereas the version of the JVAS used in this study utilized 20/40 as the pass threshold for this age group. Bringing JVAS screening thresholds into line with gold standard failure criteria (Table 1) by lowering the JVAS pass threshold for 3-year-olds to 20/50 and raising the pass threshold for 5-year-olds to 20/32, should improve specificity and sensitivity of the JVAS, respectively.…”
Section: Discussionmentioning
confidence: 98%
“…Failure on the gold standard examination was based on updated American Association for Pediatric Ophthalmology and Strabismus Vision Screening Guidelines (Table 1), 4 with visual acuity failure based on the most recent normative pediatric visual acuity data as published by Pan and colleagues 13 for children aged 30-72 months and Drover and colleagues 14 for children aged ≥72 months (Table 1). In this way, our study evaluated the ability of the JVAS to detect reduced visual acuity, amblyopia, and amblyopia risk factors.…”
Section: Gold Standard Failure Criteriamentioning
confidence: 99%
“…The spectacles prescribed fully corrected myopia > 0.75 diopters, astigmatism > 1.50 diopters and anisometropia > 1.00 diopters and either fully corrected or symmetrically under-corrected (by up to 1.50 D) hyperopia of > +3.50 D (spherical equivalent). Spectacle-corrected distance visual acuity was measured at 3M in the patients' habitual head position using the amblyopia treatment study (ATS) HOTV protocol for patients < 7 years and the ATS ETDRS protocol for patients > 7 years of age at least every 4 (+1) weeks after spectacle wear until acuity remained at within 1 line from the prior visit [23]. The visit at which visual acuity remained stable became the baseline for all further measurements.…”
Section: Interventionsmentioning
confidence: 99%